Comparative analysis of repetitive sequences among species from the potato and the tomato clades. (22nd October 2018) - Gaiero, Paola; Vaio, Magdalena; Peters, Sander A; Schranz, M Eric; de Jong, Hans; Speranza, Pablo R
Abstract: Background and Aims: The genus Solanum includes important vegetable crops and their wild relatives. Introgression of their useful traits into elite cultivars requires effective recombination between hom(e)ologues, which is partially determined by genome sequence differentiation. In this study we compared the repetitive genome fractions of wild and cultivated species of the potato and tomato clades in a phylogenetic context. Methods: Genome skimming followed by a clustering approach was used as implemented in the RepeatExplorer pipeline. Repeat classes were annotated and the sequences of their main domains were compared. Key Results: Repeat abundance and genome size were correlated and the larger genomes of species in the tomato clade were found to contain a higher proportion of unclassified elements. Families and lineages of repetitive elements were largely conserved between the clades, but their relative proportions differed. The most abundant repeats were Ty3/ Gypsy elements. Striking differences in abundance were found in the highly dynamic Ty3/ Gypsy Chromoviruses and Ty1/ Copia Tork elements. Within the potato clade, early branching Solanum cardiophyllum showed a divergent repeat profile. There were also contrasts between cultivated and wild potatoes, mostly due to satellite amplification in the cultivated species. Interspersed repeat profiles were very similar among potatoes. The repeat profile of Solanum etuberosum was more similar to that of the potato clade. Conclusions: The repeat profiles in Solanum seem to be very similar despite genome differentiation at the level of collinearity. Removal of transposable elements by unequal recombination may have been responsible for structural rearrangements across the tomato clade. Sequence variability in the tomato clade is congruent with clade-specific amplification of repeats after its divergence from S. etuberosum and potatoes. The low differentiation among potato and its wild relatives at the level of interspersed repeats may explain the difficulty in discriminating their genomes by genomic in situ hybridization techniques.